Pětiválcový řadový vznětový motor - Kujawa, Pawel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Cílem této diplomové práce je návrh klikového ústrojí podle zadaných parametrů. Práce obsahuje návrh vyvážení setrvačných sil a jejich momentů, modální analýzu a výpočet torzních kmitů. Nakonec je proveden výpočet součinitele bezpečnosti použitím MKP.

The primary objective of this thesis was to design a crankshaft according to given parameters. In this case the thesis also contains the balancing of inertia forces and its moments, modal analysis and calculation of torsion vibrations. The last chapter includes a calculation of the safety factor by using a Finite Element Method.
Five-cylinder in-line diesel engine
Keywords: klikové ústrojí; vyvažování; torzní kmity; součinitel bezpečnosti.; powertrain; balancing; torsion vibrations; safety factor.